The Effect of Anxiety and Classroom Interaction on English Speaking Performance - Fachrukrozie Kodri (Universitas Lancang Kuning, 2018)
This experimental study aims to investigate the effect of anxiety and classroom interaction on English speaking performance. This research was conducted in Perbanas Institute-Jakarta involving 32 students who were selected using simple random sampling. Using Foreign Language Classroom Anxiety Scale (FLCAS), 16 students were identified as students with high anxiety and 16 other students were grouped as students with low anxiety. Then, in practicing speaking skill, a combination of students with low and high anxiety were regrouped into the controlled group which was dominated by lecturer-learners interaction and experimental group which was dominated by learner-learners interaction. Using 2 X 2 two-way anova, the data was analysed. The findings revealed that: first, the anxiety influenced the English speaking performance; second, the classroom interaction affected English speaking performance; however, there was no interaction between anxiety and classroom interaction on English speaking performance.